Endogenous CRISPR-Cas Systems in Group I Clostridium botulinum and Clostridium sporogenes Do Not Directly Target the Botulinum Neurotoxin Gene Cluster - Wentz, Travis G.; Tremblay, Benjamin J. M.; Bradshaw, Marite; Doxey, Andrew C.; Sharma, Shashi K.; Sauer, John-Demian; Pellett, Sabine (Frontiers in Microbiology, 2022)
Most strains of proteolytic group I Clostridium botulinum (G1 C. botulinum) and some strains of Clostridium sporogenes possess genes encoding botulinum neurotoxin (BoNT), a potent neuroparalytic agent. Within G1 C. botulinum, conserved bont gene clusters of three major toxin serotypes (bont/A/B/F) can be found on conjugative plasmids and/or within chromosomal pathogenicity islands. CRISPR-Cas systems enable site-specific targeting of previously encountered mobile genetic elements (MGE) such as plasmids and bacteriophage through the creation of a spacer library complementary to protospacers within the MGEs. To examine whether endogenous CRISPR-Cas systems restrict the transfer of bont gene clusters across strains we conducted a bioinformatic analysis profiling endogenous CRISPR-Cas systems from 241 G1 C. botulinum and C. sporogenes strains. Approximately 6,200 CRISPR spacers were identified across the strains and Type I-B, III-A/B/D cas genes and CRISPR array features were identified in 83% of the strains. Mapping the predicted spacers against the masked strain and RefSeq plasmid dataset identified 56,000 spacer–protospacer matches. While spacers mapped heavily to targets within bont(+) plasmids, no protospacers were identified within the bont gene clusters. These results indicate the toxin is not a direct target of CRISPR-Cas but the plasmids predominantly responsible for its mobilization are. Finally, while the presence of a CRISPR-Cas system did not reliably indicate the presence or absence of a bont gene cluster, comparative genomics across strains indicates they often occupy the same hypervariable loci common to both species, potentially suggesting similar mechanisms are involved in the acquisition and curation of both genomic features.